Targeting an engineered cytokine with interleukin-2 and interleukin-15 activity to the neovasculature of solid tumors - Mortensen, Michael R. (Oncotarget, 2020)
There is a growing interest in the antibody-based delivery of cytokines to the tumor environment as a means to boost the anti-cancer activity of tumor-resident T cells and NK cells. Here, we describe the expression and characterization of fusion proteins, featuring the L19 antibody (specific to the alternatively-spliced EDB domain of fibronectin) and an engineered cytokine with interleukin-2 and interleukin-15 properties. The cytokine moiety was fused either at the N-terminal or at the C-terminal extremity and both fusion proteins showed a selective tumor accumulation in a quantitative biodistribution experiment. The N-terminal fusion inhibited tumor growth in immunocompetent mice bearing F9 carcinomas or WEHI-164 sarcomas when used as single agent. The anticancer activity was compared to the one of the same cytokine payload used as recombinant protein or fused to an anti-hen egg lysozyme antibody, serving as negative control of irrelevant specificity in the mouse. These results indicate that the antibody-based delivery of engineered cytokines to the tumor neovasculature may mediate a potent anticancer activity.